(untitled) (People’s Journal of Management, 2023)
A canteen serves as a venue for the serving and consumption of food, where a diverse range of snacks and beverages are available for purchase. This purpose of the study was to examine student satisfaction with campus canteen services at People’s Campus. A sample of 123 randomly selected bachelor-level students was utilized, and a descriptive research design with mean as the primary data analysis tool was employed. Data were collected through a validated questionnaire. The findings revealed an overall mean rating of 3.28, indicating that the level of student satisfaction with the canteen was moderately satisfactory. These results suggested the need for addressing canteen quality to enhance service for its student customers.